2008
DOI: 10.1111/j.1464-5491.2008.02574.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with Type 1 diabetes: a comparison of general and diabetes‐specific measures and support for a unitary diabetes quality‐of‐life construct

Abstract: Aims To assess the factor structure of the PedsQL Diabetes Module, and to compare the PedsQL general and diabetes-specific quality of life (QOL) measures regarding psychometric properties and relations to relevant outcomes. Methods The instruments were completed by 447 children age 9 to 15.5 with type 1 diabetes >1 year from four US paediatric diabetes clinics; parents completed the parallel parent-proxy measures. Principal components factor analysis was used to examine the factor structure of the PedsQL dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
58
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 25 publications
17
58
0
1
Order By: Relevance
“…A 5-cluster solution explained only ~43% of the total variation among item responses. Our conclusions are consistent with those of Nansel et al, 21 who conducted a similar analysis on responses from 447 youth with T1DM using PCA with a promax rotation and concluded that the PedsQL-T1DM total score, but not the original subscales, was the most appropriate unit for analysis. Their 5-factor structure differed from our 5-cluster solution, perhaps because of differences in analytic approaches or study populations.…”
Section: Discussionsupporting
confidence: 91%
“…A 5-cluster solution explained only ~43% of the total variation among item responses. Our conclusions are consistent with those of Nansel et al, 21 who conducted a similar analysis on responses from 447 youth with T1DM using PCA with a promax rotation and concluded that the PedsQL-T1DM total score, but not the original subscales, was the most appropriate unit for analysis. Their 5-factor structure differed from our 5-cluster solution, perhaps because of differences in analytic approaches or study populations.…”
Section: Discussionsupporting
confidence: 91%
“…The PedsQL™ Generic Core Scales and Diabetes Module are psychometrically sound [18, 32], and internal consistency was adequate in this sample (Generic Core Scales: adolescent: α=0.87, caregivers: α=0.87; Diabetes Module: adolescent: α=0.71, caregivers: α=0.74). Mean scores are summarized in Table 2 and are similar to published reports in other convenience samples [24]. …”
Section: Methodssupporting
confidence: 79%
“…This approach to QOL measurement may not represent all aspects of adolescents’ QOL, and Nansel and colleagues [24] noted concerns with individual subscale reliability. As such, results may vary with the inclusion of all PedsQL™ scale scores.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers especially, but also fathers, assessed their child's HRQOL differently than the children themselves, which is line with earlier studies [21,27]. The fathers in the intervention group had lower estimates of their child's worry than the fathers in the control group; this was true both at six and 24 months.…”
Section: Discussionsupporting
confidence: 79%